Prarancangan Pabrik Etilen Karbonat dari Etilen Oksida dan Karbon Dioksida Kapasitas 25.000 Ton/Tahun - Azzahra, Rikza Jihada, Tri Widayatno,S.T., MS.c., Ph.D, Ir. Ahmad M.Fuadi, M.T., Ph.D (2017)
The ethylene carbonate (C3H4O3) plant with ethylene oxide and carbon dioxide feedstock with a capacity of 25.000 ton/year is planned to operate for 330 days per year and is planned to be established in 2020 in the Cilegon area of Banten. The process of preparing ethylene carbonate is carried out in a bubble reactor with a water cooler. The reaction takes place in the gas-liquid phase exotermic, isothermal and non adiabatic. The reactor is run at a temperature of 160oC and a pressure of 80 atm. The need of ethylene oxide used by ethylene carbonate factory is 1.607,2043 kg/hour and carbon dioxide 1.766,1990 kg/hour using trimethylamine (TMA) catalyst as much as 10.7146 kg/hour. Ethylene carbonate product is 3,156,5656 kg/hour. The process support utility includes the process covering water supply of 1.6724,2185 kg/hour. Total make up water used is 14.616,4046 kg/hour, make up of water for steam requirement equal to 534,6166 kg/hour, compressed air 60,912 m3/hour, electricity equal to 110,9368 kW and fuel equal to 0,060 m3/hour . This ethylene carbonate plant has fixed capital investment (FCI) of Rp 16.,729.356.416 for working capital (WC) of Rp 58.614.054.739. From the economic analysis can be shown that the return on invesment (ROI) before tax 55,96% and ROI after tax 41,97%. Pay out time (POT) before tax of 1,52 years and POT after tax is 1,92 years. Break event point (BEP) of 41,81%. Shut down point (SDP) of 26,22% and discounted cash flow (DCF) of 58,37%. From the above economic analysis it is concluded that this ethylene carbonate plant is feasible to be established in Indonesia.